Nature and community. Cosmopoetic and cosmopolitical alliances with the earth from San Cristóbal – Colombia - Parra-Valencia, Liliana (2023)
We share the reflections on nature and community product of the research project on the relationship with nature in afro-descendant communities (Colombia - Brazil). It is a descriptive qualitative research, which follows participatory and collaborative methodologies, based on interviews, tours of the territory, daily conversations, musical expressions and participant observation; with counselors, traditional doctors, musicians and dancers of son de negro and bullerengue, from the San Cristóbal community (Bolívar - Colombia). We built three categories on the community's relationship with the nature: she is everything; animals, plants and everyday life; and, singing, dancing and nature. Being with the community makes it possible to produce psychologies that inhabit other humanities and forms of existence, non-anthropocentric. In a common and daily exchange, capable of poetizing life, singing verses and songs, and listening to the first music, from cosmopoetic and cosmopolitical alliances with the earth.